Biosynthesis and characterization of chitosan based hydrogel: A potential in vitro wound healing agent. (2022) - Arulmoorthy, M.P.; Anbarasi, G.; Srinivasan, M.; Vishnupriya, B.
Abstract: Humans are continuously plagued by number of new uncured diseases, resulting in the search of new medicines with zero level side effects. In the present study, an attempt has been made to prepare, characterize and to test the wound healing activity of chitosan based hydrogel. Shrimp shells was collected from Cuddalore (Lat 11° 42́ N Long 79° 46́ E), Annankovil (Lat. 11°30.47 N; Long. 079°47. 02E) and Mudasalodai landing centre (11 o 29 ′N 79 o 46 ′E) (Southeast coast of India) for extraction of chitin and chitosan and further characterized by FTIR, 1 H – NMR, DSC, SEM and XRD. Poly Ethylene Glycol (PEG) is used as a cross linking agent for the preparation of chitosan hydrogel. The prepared hydrogel was characterized by FTIR, SEM, DSC and its swelling property was tested. Synthesized chitosan hydrogel was shown very good level of growth inhibition activity against human pathogens and wound healing activity within 12 h to 24 h. Thus the present study suggests the possibility of utilizing seafood waste of crustacean shells for the extraction and preparation of useful biologically active compounds like hydrogel for medicinal drug delivery and therapeutic applications.